2021
DOI: 10.3390/cells10082170
|View full text |Cite
|
Sign up to set email alerts
|

Roles of IgE and Histamine in Mast Cell Maturation

Abstract: Mast cells are activated upon immunoglobulin E (IgE)-mediated antigen stimulation, and release a wide variety of mediators, including histamine to trigger inflammatory responses. The surface expression levels of Fce receptor I (FceRI), a high affinity receptor of IgE, were found to be positively regulated by IgE. IgE could protect murine cultured mast cells from apoptotic cell death induced by the deprivation of interleukin-3 and a certain kind of IgE could activate immature mast cells in the absence of antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 115 publications
(149 reference statements)
0
27
0
Order By: Relevance
“…Degranulation in mast cells is activated by allergens or IgE and results in the release of inflammatory mediators such as histamine, β-hexosaminidase, and cytokines [ 7 , 47 ]. These inflammatory mediators can induce allergic reaction-linked pathological events, such as skin barrier abnormalities and/or immune dysregulation in AD [ 10 , 11 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Degranulation in mast cells is activated by allergens or IgE and results in the release of inflammatory mediators such as histamine, β-hexosaminidase, and cytokines [ 7 , 47 ]. These inflammatory mediators can induce allergic reaction-linked pathological events, such as skin barrier abnormalities and/or immune dysregulation in AD [ 10 , 11 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mobile monovalent ligand showed a high density of mobile receptors, in which thousands of mobile receptors were densely packed in the centralized region of the ventral membrane, despite the lack of direct crosslinking [ 23 ]. With regard to the un-crosslinked IgE–FcεRI bearing, several studies using IgE clones indicated/discussed mechanisms underlying the effect of IgE in the absence of Ags [ 44 , 45 ], which have been proposed that the IgE–FcεRI could be clustering and internalize without Ag, suggested that the importance of Fab regions of IgE for triggering the IgE-mediated robust activation of MCs (reviewed in [ 46 ]). Although the mechanism of un-crosslinked internalization of FcεRI is still being investigated, such studies will likely be found to have important implications for further characterization of the size, mobility, and density of FcεRI clusters.…”
Section: Fcεrimentioning
confidence: 99%
“…Indeed, instances have been documented where allergens are not needed to induce an allergic response, with so-called "cytokinergic" IgE being solely responsible for the activation of MC in the absence of allergen [30]. Absence of any allergenic activity was present in the MC purified IgE aggregates, as well as in the adventitious formation of IgE aggregates from monomeric IgE ex vivo that had not been stimulated [42][43][44]. Due to 1:1 stoichiometry between the IgE and FcεRI, antigen cross-linking will bring together and stabilize multiple FcεRI, a mechanism that is known to memorize signaling-competent conformations [41].…”
Section: Drug Desensitization: Positive and Negative Role Of Mast Cellsmentioning
confidence: 99%